Co morbidities among cataract- operated patients in Rural Nepal - Shrestha, Eliya; Adhikari, Hari Bikram; Maharjan, Indra Man; Gurung, Babita (Nepalese Journal of Ophthalmology, 2018)
Introduction: Himalaya Eye Hospital (HEH), established in 1993, is providing eye care services in Gandaki, Dhaulagiri and Karnali zones. It has been providing surgical and nonsurgical eye camps in rural areas of Gandaki, Dhaulagiri and Karnali zones. The aim of this study was to determine the prevalence of ocular and systemic co morbidities among the persons treated in rural Asian setting. Method: This is the prospective non-interventional study. Patients who came to take services in surgical eye camp in rural area of Nepal were included. Data were collected by interviewing the patients. They were interviewed by local volunteers with he questionnaires prepared in English language. The volunteers were explained about the medical terminology and they interviewed the patients in native language. Result: Out of 675 patients 401(59%) had systemic co morbidities. Back pain and arthritis being the most common with 321(48%) and 260(38%) respectively. Conclusion: This study shows the systemic co morbidities among the patients who came to seek ocular treatment in eye camp in rural area of Nepal. We should do this kind of studies in different area of Nepal. These kinds of study give us total burden of systemic morbidity and help to treat accordingly.